(3EOGQI GdehGQO GdHTQjI (B/s - (3GdUjQaj, eMeO YHO GdaJGMs ((3YeGf(B: s (3OGQ GdefGgL ddfTQ hGdJhRjY(B, s, 2006)
(3jVe GdeaGgje hGdeHGOF, JNWjW Gdbhi GdYGedI, JMdjd GdhXGFa, JNWjW Gdbhi GdYGedI, JMdjd gjcd GdYeGdI, SjGSI GdENJjGQ hGdJYjjf, Jbjje GdhXGFa, gjcd GdCLhQ(B.s
Keywords: (3EOGQI GdCaQGOs; (3GdEOGQIs; (3Gdbhi GdYGedIs